2017
DOI: 10.1016/j.abb.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of 2,3-diketogulonate delay peroxidase action and induce non-enzymic H 2 O 2 generation: Potential roles in the plant cell wall

Abstract: A proportion of the plant's l-ascorbate (vitamin C) occurs in the apoplast, where it and its metabolites may act as pro-oxidants and anti-oxidants. One ascorbate metabolite is 2,3-diketogulonate (DKG), preparations of which can non-enzymically generate H2O2 and delay peroxidase action on aromatic substrates. As DKG itself generates several by-products, we characterised these and their ability to generate H2O2 and delay peroxidase action.DKG preparations rapidly produced a by-product, compound (1), with λmax 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
2
25
0
1
Order By: Relevance
“…The apparent loss in the total VC amount can be ascribed to those converted into other irreversible DHA metabolites. 17 Indeed, we have confirmed that these metabolites can be distinguished from the DHA-ASC pair on the same chromatograph (see the ESI - Fig. S3 †), further bolstering the specificity of the method.…”
supporting
confidence: 66%
“…The apparent loss in the total VC amount can be ascribed to those converted into other irreversible DHA metabolites. 17 Indeed, we have confirmed that these metabolites can be distinguished from the DHA-ASC pair on the same chromatograph (see the ESI - Fig. S3 †), further bolstering the specificity of the method.…”
supporting
confidence: 66%
“…Arabidopsis has a family of germin‐like proteins, which do not have oxalate oxidase activity (Membré et al ., ), but which may have SOD activity. Oxalate is a product of ascorbate degradation in the cell wall, but it is also potentially relevant that oxidation products of ascorbate (dehydroascorbate (DHA) and 2,3‐diketogulonate) can be degraded under apoplastic conditions with non‐enzymatic H 2 O 2 production (Kärkönen et al ., ). Very interestingly, a currently unidentified oxidation product of ascorbate also inhibits peroxidase activity (Kärkönen et al ., ).…”
Section: Production Of H2o2: Enzymes and Subcellular Locationsmentioning
confidence: 97%
“…Oxalate is a product of ascorbate degradation in the cell wall, but it is also potentially relevant that oxidation products of ascorbate (dehydroascorbate (DHA) and 2,3‐diketogulonate) can be degraded under apoplastic conditions with non‐enzymatic H 2 O 2 production (Kärkönen et al ., ). Very interestingly, a currently unidentified oxidation product of ascorbate also inhibits peroxidase activity (Kärkönen et al ., ). Cell wall ascorbate oxidase maintains ascorbate in a relatively oxidized state, and its activity could therefore influence H 2 O 2 production.…”
Section: Production Of H2o2: Enzymes and Subcellular Locationsmentioning
confidence: 97%
“…In preliminary work, we showed that radioactivity from [ 14 C]DHA was incorporated into the cellular polymeric fraction (AIR) (Figure S1). However, DHA has diverse metabolic fates, forming cOxT, OxT and OxA, as well as diketogulonate and its downstream products (Kärkönen et al ., ). We therefore focused on the incorporation of one specific naturally occurring DHA catabolite, OxT.…”
Section: Resultsmentioning
confidence: 97%